Multicentre, randomised waitlist control trial investigating a parent-assisted social skills group programme for adolescents with brain injuries: protocol for the friends project. Issue 8 (27th August 2019) - Gilmore, Rose; Sakzewski, Leanne; Ziviani, Jenny; Mcintyre, Sarah; Smithers Sheedy, Hayley; Hilton, Nicola; Williams, Tracey; Quinn, Kirsten; Sarandrea, Anne Marie; Laugeson, Elizabeth; Chatfield, Mark
Abstract : Introduction: Adolescents with brain injury frequently have difficulties with social competence, which persist into adulthood affecting their participation in daily life. To date, there has been limited research into the efficacy of social competence interventions in this population. Research from the Program for the Education and Enrichment of Relational Skills (PEERS) has demonstrated significant improvements in social competence skills, maintained at 1-year to 5-year follow-up, for adolescents with autism spectrum disorder. PEERS has not yet been tested among adolescents with brain injury. This protocol describes a pragmatic, parallel two-group pre-test post-test randomised waitlist control trial across two sites in Australia, which aims to evaluate the feasibility, acceptability and efficacy of PEERS in adolescents with brain injury compared with usual care. Methods and analysis: Forty adolescents with an acquired brain injury or cerebral palsy will be randomly assigned to either the 14-week PEERS group or waitlist care as usual group. The waitlist group will then receive PEERS following the 26-week retention time point. Outcomes will be assessed at baseline, 14 weeks (immediately postintervention) and 26 weeks follow-up (retention). The primary outcomes are self-report and parent report on the Social Skills Improvement System Rating Scales immediately post PEERS at 14 weeks. Secondary outcomes include increased frequency of get-togethers with peers with reduced conflict and increased adolescent self-reported knowledge of social skills. Acceptability and feasibility will be examined through qualitative analysis of focus group data collected after the completion of each group. Ethics and dissemination: Ethics approval has been granted by the Medical Research Ethics Committee Children's Health Queensland Hospital and Health Service Human Research Ethics Committee (HREC/17/QRCH/87), The University of Queensland (2017000864) and the Cerebral Palsy Alliance Ethics Committee (20170802/HREC:EC00402). The findings will be disseminated in peer-reviewed journals, by conference presentation and newsletters to consumers. Trial registration number: ACTRN12617000723381.